Kehidupan Keluarga Buruh Tani Rumput Laut di Pesisir Desa Lasitae Kabupaten Barru - Ernawati S. Kaseng (Rayhan Intermedia, 2022)
Farm workers' families are synonymous with poverty because they do not have the ability to meet basic needs continuously. Poverty is a characteristic of some farm workers' families in general. However, this phenomenon is different from the seaweed farm laborers found on the coast of Lasitae Village, it can be seen that some of the farm workers' families have a good daily life in terms of meeting basic needs for their families. Based on these assumptions, the objectives of this research are to find out the socio-economic life of the seaweed farm workers' families; as well as to find out strategies in meeting the living needs of families of seaweed farm workers on the coast of Lasitae Village, Barru Regency. This research is a qualitative descriptive study. The technique of taking informants was done by purposive sampling. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis techniques using qualitative descriptive analysis techniques. The results of this study indicate that the family income of seaweed farm workers received per month for the husband is the family's main income and for the wife the income received per month is additional family income. Although the income from working as farm laborers has brought changes and improvements in the socioeconomic conditions of their families, especially in terms of their children's education and housing conditions, from a health perspective they still cannot be called traditional because some of the families of farm workers still drink alcohol. traditional medicine compared to going to the puskesmas for treatment, and in terms of clothing, their food is still minimal. The active strategy carried out by several seaweed farm workers is to look for side jobs. The side job that was carried out was loading and unloading fish at the village fish auction, while the active strategy carried out by family members of seaweed farm workers, namely the wives and children encountered in the study who did not join their husbands as farm laborers, was to work together to help increase family income, by opening their own business. The passive strategy of several families of seaweed farm workers, namely by doing a frugal pattern in the daily life of the family. Then the network strategy carried out by several farm labor families, namely by borrowing money from relatives.